2001
DOI: 10.4049/jimmunol.167.9.4844
|View full text |Cite
|
Sign up to set email alerts
|

Primary Tumor Tissue Lysates Are Enriched in Heat Shock Proteins and Induce the Maturation of Human Dendritic Cells

Abstract: Upon exposure to lysates or supernatants of necrotic transformed cell lines, human dendritic cells (DCs) undergo maturation. In contrast, DCs exposed to apoptotic transformed cell lines or necrotic lysates of primary cells remain immature. Analysis of supernatants of necrotic transformed cell lines showed them to be enriched in the heat shock proteins (hsp)70 and gp96, in contrast to supernatants of primary cells. Likewise, cells from a variety of primary human tumors contained considerably higher levels of hs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
131
0
5

Year Published

2004
2004
2007
2007

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(142 citation statements)
references
References 53 publications
6
131
0
5
Order By: Relevance
“…The exact nature of these ablation- dependent signals need further clarification, but may well represent cytokines or other endogenous mediators released after ablation (de Jong et al, 2001;Huang et al, 2002;Pasare and Medzhitov, 2004;Sporri and Reis e Sousa, 2005). It has, for instance, been shown that heat shock proteins and uric acid are present in cell debris, which both influence DC and other parts of the immune system (Somersan et al, 2001;Shi et al, 2003). Importantly, the observed ablation-induced increase in the number and maturation state of antigen-loaded DC is apparently not sufficient to induce complete tumour protection of mice.…”
Section: Discussionmentioning
confidence: 99%
“…The exact nature of these ablation- dependent signals need further clarification, but may well represent cytokines or other endogenous mediators released after ablation (de Jong et al, 2001;Huang et al, 2002;Pasare and Medzhitov, 2004;Sporri and Reis e Sousa, 2005). It has, for instance, been shown that heat shock proteins and uric acid are present in cell debris, which both influence DC and other parts of the immune system (Somersan et al, 2001;Shi et al, 2003). Importantly, the observed ablation-induced increase in the number and maturation state of antigen-loaded DC is apparently not sufficient to induce complete tumour protection of mice.…”
Section: Discussionmentioning
confidence: 99%
“…HSP70 has been reported to activate the innate immune response, resulting in the maturation of DCs, [13][14][15] the upregulation of proinflammatory cytokines [13][14][15][16] and nitric oxide release by APCs. 17 Rapid intracellular Ca 2 þ flux 18 and CD14-dependent toll-like receptor (TLR) 2-and TLR4-mediated activation of the MyD88/interleukin-1 receptor associated kinase (IRAK)/nuclear factor (NF)-kappaB signal transduction pathway 18,19 have been reported as consequences of HSP70 binding to cell surface receptors on APCs.…”
Section: Introductionmentioning
confidence: 99%
“…Several phases have been characterized in programmed cell death 35,36 from the early phase of PS exposure on the cell surfaces to the late phase, defined as secondary necrosis, and characterized by the cell membrane damage revealed by using PI staining 36 and the expression of HSP. 37 Heat shock proteins belong to a family of chaperone proteins, the key elements in the protein-folding machinery of the cells.…”
Section: Discussionmentioning
confidence: 99%